2023
DOI: 10.1101/2023.02.10.23285783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenome-wide Investigation of Behavioral, Environmental, and Neural Associations with Cross-Disorder Genetic Liability in Youth of European Ancestry

Abstract: Etiologic insights into psychopathology may be gained by using hypothesis-free methods to identify associations between genetic risk for broad psychopathology and phenotypes measured during adolescence, including both markers of child psychopathology and intermediate phenotypes such as neural structure that may link genetic risk with outcomes. We conducted a phenome-wide association study (phenotype n=1,269-1,694) of polygenic risk scores (PRS) for broad spectrum psychopathology (i.e., Compulsive, Psychotic, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Based on previous GWAS of externalizing and internalizing 14,15,83 and existing theory, 7,9 we considered a total of 18 externalizing and internalizing traits for inclusion in the analyses (Supplementary Figure 1). We excluded two traits (automobile speeding propensity and anorexia nervosa) that were weakly associated with the others in the model (mean r g < 0.20).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous GWAS of externalizing and internalizing 14,15,83 and existing theory, 7,9 we considered a total of 18 externalizing and internalizing traits for inclusion in the analyses (Supplementary Figure 1). We excluded two traits (automobile speeding propensity and anorexia nervosa) that were weakly associated with the others in the model (mean r g < 0.20).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, across ancestries, common genetic risk partially accounted for the shared features of BD and SCZ. Other gSEM studies have also showed that SCZ and BD load onto the same genetic factor, 18,[70][71][72] highlighting their strong shared etiology despite belonging to different diagnostic classes. Although smaller samples and greater genetic diversity limited statistical power to replicate the EUR factor structure in AFR individuals, there were significant commonalities across genetic ancestry groups.…”
Section: Identification Of Suds Psychotic and Mood Disorder Factorsmentioning
confidence: 97%